Pemanfaatan Sarana Prasarana dalam Pelaksanaan Bimbingan Konseling di Sekolah - Azmatul Khairiah Sari; Neviyarni Neviyarni; Riska Ahmad; Yarmis Syukur (Universitas Lampung, 2021)
Infrastructure facilities are essentially a support in the implementation of an educational process or the implementation of counseling guidance. Without the infrastructure, the implementation of counseling guidance will be constrained and the goals to be achieved are not as expected. If the infrastructure does not exist in an educational institution, it will cause counseling guidance personnel in schools to have difficulty collaborating in the implementation of counseling guidance in schools. From that counseling guidance requires facilities and infrastructure to be used in the implementation of counseling guidance in schools.